Studying modern Arabic literature : Mustafa Badawi, scholar and critic - Allen, Roger, 1942-; Ostle, Robin (Edinburgh University Press, 2015)
Shows how the study of modern Arabic literature was transformed by Mustafa Badawi Prior to the 1960s the study of Arabic literature, both Classical and Modern, had barely been emancipated from the academic approaches of Orientalism. The appointment of Mustafa Badawi as Oxford University's first Lecturer in Modern Arabic Literature changed the face of this subject as Badawi showed, through his teaching and research that Arabic literature was making vibrant contributions to global culture and thought. Part biography, part collection of critical essays, this volume celebrates Badawi's immense contribution to the field and explores his role as a public intellectual in the Arab world and the west. Key Features Illustrates the critical affiliations and teaching methods of the outstanding scholar of modern Arabic literature in the 20th century Assesses some of the problems faced by an outstanding intellectual and translator in bridging Arabic and western cultures Includes studies from eminent specialists who were taught by Badawi, showing the type of work he inspired, including Julia Bray, Hilary Kilpatrick, Marliyn Booth, Miriam Cooke and Paul Starkey